Índice de potencial productivo del suelo aplicado a tres fincas ganaderas de ladera en el Valle del Cauca, Colombia Livestock productive potential in the hillside areas of Cauca Valley, Colombia - Adriana Rojas Palomino (Acta Agronómica, 2009)
Se evaluó el potencial productivo-PPS en suelos volcánicos de ladera de tres fincas lecheras (Nogales, Refugio y Horizonte) en Bolívar, Valle del Cauca, utilizando un indicador mixto de propiedades (físicas, químicas y de actividad biológica del suelo), conductividad térmica y el efecto de manejo con los índices de Compactación (IC) y Fertilidad (IF). Se utilizó un diseño completamente al azar con tres tratamientos y cinco repeticiones de acuerdo con zonas homogéneas de humedad edáfica. IC fue moderado en todos los casos y PPS fue medio en las tres fincas no obstante el IF fuera alto en Nogales y moderado en Refugio y Horizonte. La correlación lineal múltiple entre parámetros indicó que IC e IF influyeron aproximadamente en un 70 % sobre PPS. The productive potential (PP) of three dairy farms with volcanic soils, located in hillside areas of Bolivar, Valle del Cauca, Colombia, was evaluated using a mixed indicator that assessed the soil's physical and chemical properties as well as its biological activity, including a new characteristic-thermal conductivity sensitive to soil quality. The effect of management on soil fertility and compaction was also assessed using two new soil indicators: compaction and fertility. A completely randomized design was used, with farms corresponding to the treatments. The replicates on each farm were carried out according to homogeneous areas of soil moisture. The results for each indicator agreed with the individual analysis of soil properties. Compaction was moderate in all cases and PP was intermediate on the three farms, although soil fertility was high in Nogales and moderate in Refugio and Horizonte. The multiple linear correlation between these parameters indicated that compaction and fertility accounted for approximately 70% of the PP.